Preparation and Reactivity Studies of Four and Five coordinated Amidinate Aluminum Compounds. Issue 18 (21st May 2021) - Banerjee, Samya; Kumar, Chowan Ashok; Bose, Sanjoy; Sarkar, Samir Kumar; Gupta, Sandeep K; Graw, Nico; Köhler, Christian; Herbst‐Irmer, Regine; Stalke, Dietmar; Dutta, Sayan; Koley, Debasis; Roesky, Herbert W.
Abstract: Synthesis of four and five coordinated aluminum amidinate (PhC(N t Bu)2 =L) compounds are reported herein along with their single‐crystal X‐ray structures and detailed characterizations using both, experimental and computational techniques. LAlCl2 (1 ) and L2 AlCl (2 ) were synthesized by treating AlCl3 with PhC(N t Bu)2 Li in an equivalent ratio of 1 : 1 and 1 : 2, respectively. [LAl(C2 H5 )Cl] (3 ) was prepared from a reaction of AlCl2 (C2 H5 ) with PhC(N t Bu)2 Li in an equivalent ratio of 1 : 1. Reactivity of 3, an amidinate based organo‐aluminum compound is explored for the various reactions. 3 produced [LAl(C2 H5 )(μ‐F)]2 (4 ) on treatment with Me3 SnF. Interestingly, [LAl(C2 H5 )Cl] (3 ) was converted to [LAlCl(μ‐OEt)]2 (5 ) when refluxed in Et2 O. 3 gives the monomeric and neutral cyclic (alkyl)(amino) carbene (cAAC) based radical [LAl(C2 H5 )(cAAC)] (6 ) on reduction with KC8 in the presence of cAAC. Abstract :